Isotropic exchange interaction between Mo and the proximal FeS center in the xanthine oxidase family member aldehyde oxidoreductase from Desulfovibrio gigas on native and polyalcohol inhibited samples: an EPR and QM/MM study - Gomez, María C. (2014)
Aldehyde oxidoreductase from Desulfovibrio gigas (DgAOR) is a homodimeric molybdenum-containing protein that catalyzes the hydroxylation of aldehydes to carboxylic acids and contains a Mo-pyranopterin active site and two FeS centers called FeS 1 and FeS 2. The electron transfer reaction inside DgAOR is proposed to be performed through a chemical pathway linking Mo and the two FeS clusters involving the pyranopterin ligand. EPR studies performed on reduced as-prepared DgAOR showed that this pathway is able to transmit very weak exchange interactions between Mo(V) and reduced FeS 1. Similar EPR studies but performed on DgAOR samples inhibited with glycerol and ethylene glycol showed that the value of the exchange coupling constant J increases ~2 times upon alcohol inhibition. Structural studies in these DgAOR samples have demonstrated that the Mo–FeS 1 bridging pathway does not show significant differences, confirming that the changes in J observed upon inhibition cannot be ascribed to structural changes associated neither with pyranopterin and FeS 1 nor with changes in the electronic structure of FeS 1, as its EPR properties remain unchanged. Theoretical calculations indicate that the changes in J detected by EPR are related to changes in the electronic structure of Mo(V) determined by the replacement of the OHx labile ligand for an alcohol molecule. Since the relationship between electron transfer rate and isotropic exchange interaction, the present results suggest that the intraenzyme electron transfer process mediated by the pyranopterin moiety is governed by a Mo ligand-based regulatory mechanism.